The Symbolism of Fire in the Classic Judaic Criminal Law - Sygit, Bogusław; Wąsik, Damian (Studia Warmińskie, 2014)
Since the dawn of history, fire was given a mystical character. Fire was associated with strength, power, mystery and the supernatural. Fire is of particular importance in the Jewish tradition and culture. The main aim of the publication is to present the symbolism of fire in Judaic criminal law, which is understood as a law arising from the Torah and the Talmud. Authors describe the subject of the treatment of fire as a kind of punishment tool and as a murder weapon. In the first case, the publication focuses on permissible in Judaism form of capital punishment by burning. In the second case authors raise the question of the principles of criminal responsibility by the perpetrators of arson. Recalling the principle of Judaic criminal law the authors argue that arson, contrary to some opinions presented in literature, should be treated as a causative action of certain crimes, and not as a separate offense.